What drives risk perception? A global survey with financial professionals and lay people - Felix Holzmeister; Jürgen Huber; Michael Kirchler; Florian Lindner; Utz Weitzel; Stefan Zeisberger (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
Risk is an integral part of many economic decisions, and is vitally important in finance. Despite extensive research on decision-making under risk, little is known about how risks are actually perceived by financial professionals, the key players in global financial markets. In a large-scale survey experiment with 2,213 finance professionals and 4,559 lay people in nine countries representing 50% of the world's population and more than 60% of the world's gross domestic product, we expose participants to return distributions with equal expected return and we systematically vary the distributions' next three higher moments. Of these, skewness is the only moment that systematically affects financial professionals' perception of financial risk. Strikingly, variance does not influence risk perception, even though return volatility is the most common risk measure in finance in both academia and the industry. When testing other, compound risk measures, the probability to experience losses is the strongest predictor of what is perceived as being risky. Analyzing professionals' propensity to invest, skewness and loss probability have strong predictive power too. However, volatility and kurtosis also have some additional effect on participants' willingness to invest. Our results are very similar for lay people, and they are robust across and within countries with different cultural backgrounds as well as for different job fields of professionals.
Keywords: 330; Risk perception; investment propensity; financial professionals